Analysis Effectiveness of The Flip Application As A Digital Financial Service Instrument in Sharia Presfectve - Masitoh, Ika Siti; Selasi, Dini; Pratama, Gama; Mohammad Ridwan, Mohammad; Rizki Bahari, Fauzi (Journal of Islamic Economic Development, 2023)
Fintech (financial technology) is technology and innovation that increases the efficiency, effectiveness, and speed of money and investment management. Digital financial services increasingly dominate the global financial sector, along with the increasing use of technology-based applications. One of the financial service applications that makes payments easier is Flip, which offers innovative solutions to users' financial needs. Flip is a digital application that offers various ways to manage money. This application allows you to make inter-bank transfers, transfer money to various countries, purchase credit and electricity tokens, and top up e-wallet balances. The method used in this research is descriptive and qualitative using secondary literature research methods. This research aims to determine the effectiveness of the flip.id application as a tool for providing virtual currency from a Sharia perspective. The research results show that the positive impact of the Flip application is seen in easy access to inclusive finance, fulfillment of Sharia financial principles, and acceleration of financial inclusion in Muslim communities. Flip has become an important factor in developing the Sharia economy in Indonesia thanks to innovation and efforts to improve fintech, which follows Sharia financial regulations.